2006
DOI: 10.1111/j.1460-9568.2006.04627.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating insulin‐like growth factor I and functional recovery from spinal cord injury under enriched housing conditions

Abstract: Voluntary locomotor training as induced by enriched housing of rats stimulates recovery of locomotion after spinal cord injury (SCI). Generally it is thought that spinal neural networks of motor- and interneurons located in the ventral and intermediate laminae within the lumbar intumescence of the spinal cord, also referred to as central pattern generators (CPGs), are the 'producers of locomotion' and play a pivotal role in the amelioration of locomotor deficits after SCI. It has been suggested that locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…33 We acquired and studied five uninterrupted runs with the CatWalk system on the day of open field testing, considering ''consistent coordination'' when Regularity Index (RI) ( Table 1) scored 100% in 5/5 runs; ''frequent coordination'' when RI scored 100% in 3/5 or 4/5 runs; ''occasional coordination'' when RI scored 100% in 1/5 or 2/5, and ''no coordination'' when RI scored 100% in 0/5 runs. We also used the BBB subscoring scale to improved the sensitivity of the BBB by scoring the higher motor functions (i.e., toe clearance, predominant paw position, trunk stability, and tail position) regardless of the other BBB parameters, adding them together to yield a single score (maximum score = 13).…”
Section: Open-field Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 We acquired and studied five uninterrupted runs with the CatWalk system on the day of open field testing, considering ''consistent coordination'' when Regularity Index (RI) ( Table 1) scored 100% in 5/5 runs; ''frequent coordination'' when RI scored 100% in 3/5 or 4/5 runs; ''occasional coordination'' when RI scored 100% in 1/5 or 2/5, and ''no coordination'' when RI scored 100% in 0/5 runs. We also used the BBB subscoring scale to improved the sensitivity of the BBB by scoring the higher motor functions (i.e., toe clearance, predominant paw position, trunk stability, and tail position) regardless of the other BBB parameters, adding them together to yield a single score (maximum score = 13).…”
Section: Open-field Locomotionmentioning
confidence: 99%
“…Changes in PD variability represent a measure of interlimb coordination: during uninterrupted locomotion, coordinated limb pairs show very small phase dispersion variability, whereas limbs that move largely autonomously display a high variability. 33,49 We averaged the values of complementary pairs to perform statistical analysis: PD diagonal pairs is the average between left forward-right hindlimb (LF-RH) and right forward-left hindlimb (RF-LH) and PD ipsilateral pairs is the average between right forward-right hindlimb (RF-RH) and left forward-left hindlimb (LF-LH). We also estimated the PD variability of pectoral (LF-RF) and pelvic (LH-RH) girdles.…”
Section: Phase Dispersions (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that EE and physical exercise increase IGF-1 in the brain (Carro et al, 2000(Carro et al, , 2001Koopmans et al, 2006;Sale et al, 2007).…”
Section: Increased Levels Of Igf-1 In the Cortex Of Massaged Rat Pupsmentioning
confidence: 99%
“…One group of molecules particularly sensitive to experience are neurotrophins, a family of secreted factors critically involved in structural and functional plasticity during development and in adulthood [46]. An important line of research deals with the potential therapeutic effects of EE: indeed, it has been shown that enriching the housing environment delays the progression of, and facilitates recovery from, various nervous system dysfunctions, including neurodevelopmental disorders, neurodegenerative diseases, different types of brain injury and psychiatric disorders [47][48][49][50][51][52][53][54]. These studies have profound consequences for humans.…”
Section: Introductionmentioning
confidence: 99%